(Learning with a difference) Comprehension strategies primary 6 - Gurr, Brenda (Learners Press Private Australia, 2008)
Comprehension Strategies Primary 6 by Brenda Gurr offers practical techniques and exercises to help students in Primary 6 develop essential reading comprehension skills. The book focuses on improving students' ability to understand, analyze, and respond to a variety of texts through targeted strategies.